2013
DOI: 10.13000/jfmse.2013.25.4.828
|View full text |Cite
|
Sign up to set email alerts
|

The Residues of Antibiotics (Tetracycline, Oxolinic Acid and Ciplofloxacin) and Malachite Green in Cultured Rainbow Trout

Abstract: Products from aquaculture have sometimes been focused on the problems caused by the contamination of chemical agents as the use of chemical agents in aquaculture has been annually increased. The risk of contamination of products by chemical agents is greater in freshwater than in seawater. In order to evaluate the food safety of a fish grown in freshwater, we investigated the residues of antibiotics (tetracycline, oxolinic acid and ciplofloxacin) and malachite green in cultured rainbow trout, Oncorhynchus myki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In addition, the risk of contamination of products by chemical agents is greater in freshwater than in seawater (28,29). Chemical agents such as malachite green and crystal violet are not approved worldwide as veterinary drugs for fish because of their carcinogenicity and mutagenicity (30), but such agents are used illegally due to their low cost and high efficiency (31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the risk of contamination of products by chemical agents is greater in freshwater than in seawater (28,29). Chemical agents such as malachite green and crystal violet are not approved worldwide as veterinary drugs for fish because of their carcinogenicity and mutagenicity (30), but such agents are used illegally due to their low cost and high efficiency (31).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, consumers are reluctant to consume aquaculture products that might have been exposed to hazardous chemicals or antibiotics. However, few studies have examined the levels of banned chemical and residual antibiotic in freshwater aquaculture fish (11,29). Therefore, we evaluated the levels of banned chemicals and residual antibiotics in seven freshwater aquaculture species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that these levels were below the MRL laid down in Korean Food Legislation. Furthermore Kim et al (2013) analyzed the presence of tetracycline residues in a study in trout in the Republic of Korea. Tetracycline residue was below 200 µg/kg and it was found that this level was below the MRL laid down in Korean legislation.…”
Section: Discussionmentioning
confidence: 99%